A comparative study evaluating insight in different phase of illness among patients with bipolar disorder by using multiple scales. (1st July 2021) - Choudhury, Shinjini; Avasthi, Ajit; Chakrabarti, Subho; Grover, Sandeep
Abstract: Aim: This cross-sectional study aimed to evaluate insight and its correlates among patients with bipolar disorder (BD). Methodology: 180 patients with BD were evaluated on Scale to Assess Unawareness of Mental Disorders (SUMD), Insight scale for affective disorders (ISAD), Mood Disorders Insight Scale (MDIS), and Beck Cognitive Insight Scale (BCIS). Results: About half of the patients were in clinical remission ( N = 94; 52.2%), one-fifth ( N = 37; 20.55%) were in the phase of mania and one-fourth ( N = 49; 27.2%) were in a depression. There was no significant difference in the level of insight between those in clinical remission and those in depression except for one of the domains of BCIS. Patients with mania had poorer insight compared to those in remission and depression. In terms of association of insight as assessed by different scales, in the whole sample and all the three subgroups, SUMD current and past scores had a significant positive correlation with the ISAD total score. In the whole sample, among patients currently in remission and those currently in depression, ISAD total score had significant negative correlation with MDIS total score. Poorer insight as assessed on SUMD (current and past), ISAD and MDIS was associated with poorer medication adherence. Conclusion: The present study demonstrates that patients with mania have poor insight when compared to the patients in clinical remission and depression. The present study also demonstrates that the assessment of clinical insight is not affected much by the type of scale used.